Effect of mineral fertilization and organic fertilization on pineapple [Ananas comosus (L.) Merr.] cultivar MD2 (‘Golden’) (2018)
In Peruvian pineapple cultivation, there is a lack of fertilizer studies with organic and inorganic sources. For that reason, a study was done in order to determine the influence of Alopes Forte organic fertilizer, with and without mineral fertilization, on some aspects of pineapple cultivation, such as vegetative growth, productivity, fruit quality and economic variables. The pineapple cultivar ‘Golden’ was used, which was subjected to the following treatments: T1: Control; T2: Alopes Forte (25 ‰); T3: Alopes Forte (50 ‰); T4: Alopes Forte (20 ‰) + N150-P75- K200-Mg25-Ca25; T5: Alopes Forte (20 ‰) + N250-P125-K300-Mg50-Ca50; T6: N300-P150-K400-Mg50-Ca50 and T7: N500-P250-K600-Mg100-Ca100. The results showed that there were no differences between the treatments for the number of leaves; however, treatment T7 had higher values for leaf D length and weight (fresh and dry), while treatments T4, T5, T6 and T7 presented the better result for nitrogen (leaf D). Fruit quality variables (lower, middle and upper diameter, central axis fruit diameter, number of berries per fruit, pineapple length, fruit fresh weight (with and without crown) and content of soluble solids, as well as the pineapple production income and profitability, showed the highest values in T7. These results indicate that the organic fertilizer did not influence on the evaluated variables; on the contrary, the use of synthetic fertilizers had a positive effect.